Caring in U.S. National Collegiate Athletic Association Division I Sport: The perspectives of 18 female and male head coaches - Fisher, L. A.; Bejar, M. P.; Larsen, L. K.; Fynes, J. M.; Gearity, B. T. (International Journal of Sports Science & Coaching, 2017)
The current study was undertaken to explore how U.S. National Collegiate Athletic Association Division I female and male head coaches defined and implemented care in their coaching practice. Eighteen coaches (M=39.2 years; nine females, nine males) from eight different sports (baseball, rowing, soccer, softball, swimming, track and field/cross-country, volleyball, and golf) consented to be interviewed via a semi-structured interview guide based on the care literature. Data analysis was conducted using Consensual Qualitative Research with a team of five researchers including an external auditor. Results revealed that care revolved around six domains: (a) definition of care; (b) manifestations of care; (c) limits to capacity to be caring; (d) development of care; (e) factors facilitating care, and (f) factors hindering care. Each domain contained several categories (N=22 total categories) composed of core ideas. Results are presented using participants` own words to illustrate domains and categories. Implications for research and practice are also put forth, which link the findings to the broader U.S. National Collegiate Athletic Association coaching context. ABSTRACT FROM AUTHOR